Biochemical, Microbial and Sensory Changes of Bombay duck (Harpodon nehereus) Fish Fingers during Chilled Storage - Jeyakumari, A.; Murthy, L. N.; Vishnuvinayagam, S. (Fishery Technology, 2017)
Bombay duck (Harpodon nehereus) is one of theimportant fishery species along Gujarat andMaharashtra coasts. Due to a very high moisturecontent (90%), it is unsuitable to use either in freshor in frozen form and almost entire catch isconsumed in sundried form. This study is aimed toexplore the possibilities of better utilization of thisspecies by development of battered and breaded fishfingers. Fish fingers were prepared from Bombayduck fillet and their qualities were evaluated underchilled storage up to 21 days. Fish fingers had52.43% moisture, 12.25% protein, 10.17% fat, 2.03%ash and 23.12% carbohydrate. Results showedincreasing trend in pH, TVB-N, FFA, PV and TBAvalues (p